Epidemiology of Intestinal Parasites in the Rural and Urban Areas of Hamadan Province in west -Central Iran - Mohammad Mahdi Majzoobi; Amir Hossein Maghsood; Mohammad Matini; Khosrow Sardarian; Sayed Ali Alavi; Mohammad Fallah (Shahrekord University of Medical Sciences, 2021)
Background and aims: Previous studies have shown that the intestinal parasites have the high prevalence in Hamadan province. However, this problem has not been addressed properly yet and, therefore, there is not up-to-date information about it. This study aimed to determine the prevalence of intestinal parasites in different residential areas of Hamadan Province (urban and rural areas) and compare the obtained findings with the results from previous studies on these parasites in this region and other parts of Iran.   Methods: In this cross-sectional study, a total of 2948 fecal samples were collected from all rural and urban inhabitants of the province (including 12 cities) by cluster random sampling method. Fecal samples were examined using the direct smear and formalin ether concentration techniques. A questionnaire was used to collect relevant epidemiologic information about the study population.   Results: Overall, 52.2% of the samples were from rural areas, and the rest were from urban areas. As for the gender of study population, 50.6% were male and 49.4% were female (Mean age 29±12.3). The infection rate was 4.9% for both pathogenic and non-pathogenic parasites. Only 4 specimens were positive for ova (Ascaris lumbricoides, Hymenolepis nana, and pinworm). A total of 69 specimens (2.3%) were positive for pathogenic parasites, and 73 specimens (2.5%) were positive for non-pathogenic (E. coli). The most important intestinal parasite in this region was found to be Giardia lamblia. It was also discovered that totally 2.3% of the studied population was infected with this parasite.   Conclusion: According to the results from this study, this area was not faced with a problem caused by the intestinal parasites at the time. In addition, only G. lamblia was found to have been a moderate parasitic problem in the province.